Efektīvāko risinājumu noteikšana līzinga un kreditēšanas jomā, Latvijas transporta firmai - Glazovs, Maksims (Latvijas Universitāte, 2007)
„Efektīvāko risinājumu noteikšana līzinga un kreditēšanas jomā Latijas transporta firmai”. Autors M. Glazovs. Darba vadītājs Soc.zin.maģ.ek., profesors A. Mašarskis . Darbs sociālo zinātņu maģistra vadībzinātnē akadēmiskā grāda iegūšanai: 87. lpp, 25. attēli., 10.tabulas., 34. izmantotās literatūras un citu informācijas avotu saraksts. Maģistra darbs “ Efektivāko risinājumu noteikšana līzinga un kreditēšanas jomā Latijas transporta firmai” ir patstāvīgs pētījums par līzinga finansēšanas iespējām uzņēmumā, tā attīstību Latvijā un Eiropas Savienībā, par tā tiesiskajiem aspektiem. DAŽĀDU VEIDU LĪZINGS, IETEKME DAŽĀDU VEIDU LĪZINGU UN KREDITĒŠANA UZ UZŅĒMUMIEM FINANŠU ATSKAITĒM, VISS VAIRĀK EFEKTĪVU NOTEIKŠANU LĪZINGU UN KREDITĒŠANAS VARIANTU. Maģistra darba mērķis bija veikt pētījumu par šī pakalpojuma nozīmīgumu uzņēmumā un ekonomikā kopumā, par līzinga vēsturisko attīstību, par līzinga attīstību Eiropas Savienībā, kā arī izpētīt situāciju attiecībā uz līzingu Latvijā. Darbā izpētīta evolūciju līzinga jēdziens, kā finanšu instruments, kas pietiekami plaši sāk izmantot Latvijā. Novadīti pamata raksturojums divu, viss vairāk izplatītu līzingu veidu, tieši finanšu un operatīvais līzings. Piemēram loģistikas firma „Sonora” veica salīdzinošu analīzi līzingu un kredītu finanšu instrumentus, un piedāvātu modeļu atzīmju efektivitātes izvēle to vai citu finanšu instrumentu uz vērtību pieejamās bāzes.

“Definition of the most effective decisions in the field of leasing and credit area in Latvian transport company” Author M. Glazov. Scientific Adviser M. Oec., professor A.Masharskij . The purpose of this thesis is the academic Master degree of Social Sciences in Management Science: 87. pgs, 25. fig., 10. titles, 34. list of references. VARIOUS KINDS OF LEASING, INFLUENCE OF VARIOUS KINDS OF LEASING AND CREDITING ON FINANCIAL REPORTS OF THE ENTERPRISE, DEFINITION OF THE MOST EFFECTIVE VARIANTS OF LEASING AND CREDITING Master work “ Definition of the most effective decisions in the field of leasing and credit area in Latvian transport company” is independent research of leasing , about history of leasing, opportunities of leasing at the enterprise, its development in the European union and in Latvia,about it’s legal aspects. The purpose of master work contains in finding the best decision of leasing for a transport company, to find value of leasing in economy of Latvia, in economy of the European union, to study value of leasing in Latvia, to study evolution of leasing in Latvia, leasing as the financial tool which is widely used in Latvia, in master work are described the most popular leasing types- financial and operative leasing. In work evolution of concept leasing, as financial tool, which widely enough start to use in Latvia, is investigated. Are shown the basic characteristics of two, most widespread kinds of leasing, namely financial leasing and operative leasing. On an example of furniture firm “Sonora” the comparative analysis of use of leasing and credit financial tools is lead, and the model of an estimation of efficiency of a choice of this or that financial tool on the basis of the cost approach is offered.
Effective decision making in leasing and credit area in Latvian transport company
Keywords: Ekonomika